2019
DOI: 10.48550/arxiv.1912.05784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning Improvement Heuristics for Solving Routing Problems

Abstract: Recent studies in using deep learning to solve the Travelling Salesman Problem (TSP) focus on construction heuristics, the solution of which may still be far from optimality. To improve solution quality, additional procedures such as sampling or beam search are required. However, they are still based on the same construction policy, which is less effective in refining a solution. In this paper, we propose to directly learn the improvement heuristics for solving TSP based on deep reinforcement learning. We firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Most constructive neural methods are auto-regressive, predicting the next node given the partial tour constructed, but other works have considered predicting a 'heatmap' of promising edges at once (Nowak et al, 2017;Joshi et al, 2019a;Fu et al, 2020), which allows a tour to be constructed (using sampling or beam search) without further evaluating the model. Whereas these are constructive approaches, others have reported results with 'learning to search', where a neural network is used to guide a search procedure such as local search (Chen & Tian, 2019;Lu et al, 2020;Gao et al, 2020;Wu et al, 2019;Hottung & Tierney, 2019). While most researches have focused on instances up to 100 nodes, some have attempted scaling to larger instances, which remains challenging (Ma et al, 2019;Fu et al, 2020).…”
Section: Machine Learning For Vehicle Routing Problemsmentioning
confidence: 99%
“…Most constructive neural methods are auto-regressive, predicting the next node given the partial tour constructed, but other works have considered predicting a 'heatmap' of promising edges at once (Nowak et al, 2017;Joshi et al, 2019a;Fu et al, 2020), which allows a tour to be constructed (using sampling or beam search) without further evaluating the model. Whereas these are constructive approaches, others have reported results with 'learning to search', where a neural network is used to guide a search procedure such as local search (Chen & Tian, 2019;Lu et al, 2020;Gao et al, 2020;Wu et al, 2019;Hottung & Tierney, 2019). While most researches have focused on instances up to 100 nodes, some have attempted scaling to larger instances, which remains challenging (Ma et al, 2019;Fu et al, 2020).…”
Section: Machine Learning For Vehicle Routing Problemsmentioning
confidence: 99%
“…Chen et al [29] proposed a DRL-based local search framework, termed NeuRewriter, that shows a promising performance on CVRP and job scheduling problems. Wu et al [30], and Costa et al [31] proposed a DRL-based TSP solver by learning the 2-opt. Their method improves the randomly generated solutions, unlike the method of Chen et al [29] rewrites a solution given by a conventional heuristic solver.…”
Section: Drl-based Improvement Heuristicsmentioning
confidence: 99%
“…We follow baseline setting of Kool et al [12] and Costa et al [19]. We set DRL baselines including the S2V-DQN [11], EAN [23], GAT-T [30], DRL-2opt [19], and AM [12]. We show the results of S2V-DQN and EAN reported by Kool et al [12], and the results of GAT-T reported by Costa et al [19].…”
Section: Capacitated Vehicle Routing Problem (Cvrp)mentioning
confidence: 99%
“…This process can then be emulated to generate (possibly smallersized) more representative CVRP instances, as it was done in Kool, Hoof, Gromicho, et al (2021) and in Hottung, Kwon, and Tierney (2021) (appendix). In Wu et al (2020), the authors directly used a subset of X instances along with distributions more commonly used in other ML works.…”
Section: Benchmark Instances and Problem Definitionmentioning
confidence: 99%
“…Currently, most of the proposed approaches aim at learning constructive heuristics, which sequentially extend a partial solution, possibly employing additional procedures such as sampling and beam search (see e.g., Bello et al (2017) and Hottung, Kwon, and Tierney (2021)). Few others, such as Wu et al (2020) and Chen and Tian (2019), instead, focus on learning improvement heuristics to guide the exploration of the search space and iteratively refine an existing solution.…”
Section: Introductionmentioning
confidence: 99%